Between politics and markets : firms, competition, and institutional change in post-Mao China - Lin, Yi-min (Structural analysis in the social sciences, 2002)
Between Politics and Markets examines how the decline of central planning in post-Mao China was related to the rise of two markets - an economic market for the exchange of products and factors, and a political market for the diversion to private interests of state assets and authorities.